Optimalisasi Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja di Lingkungan Debiddikpimkatnas Lemhannas RI - Yolanda Widya Valiria; Suhroji Adha (Universitas 45 Surabaya, 2024)
This research aims to examine the performance of employees in the Deputy for National Level Leadership Education (Debiddikpimkatnas) of Lemhannas RI, to find out the level of Organizational Culture of employees of Debiddikpimkatnas of Lemhannas RI; find out the impact of organizational training for Lemhannas RI Debiddikpimkatnas employees; see the impact of performance motivation of Lemhannas RI Debiddikpimkatnas employees. The results of the research study show that the existence of organizational culture has quite a significant influence on the performance of Debiddikpimkatnas employees, as indicated by the t significance number of 0.027 which has a value smaller than alpha = 0.05, namely (0.027 < 0.05) with a regression coefficient of 0.244. The training provided by the organization has quite a significant influence on the performance of Debiddikpimkatnas employees, as shown by the t significance number of 0.003 which has a value smaller than alpha = 0.05, namely (0.003 < 0.05) with a regression coefficient of 0.646. Motivation does not have a significant effect on the performance of Debiddikpimkatnas employees, as shown by the t significance result of 0.541 where this figure is greater than alpha = 0.05 (0.541 > 0.05) with a regression coefficient of 0.098. The cultural variables contained within an organization and the impact of training provided by the organization move simultaneously to have quite a significant influence on the performance of Lemhannas RI Debiddikpimkatnas employees, as indicated by the F coefficient significance number of 0.0001 which is lower than alpha = 0.05, namely (0.0001 < 0.05) and has been proven to contribute to employee performance as much as 53.9%, while the other 46.1% has been explained outside the research model factors.